Enterprise Diagnostics as Part of Company Management - Ďurišová, Mária (Ekonomika, 2007)
This paper deals with the key factors of enterprise diagnostics and describes research findings by abstract models. Enterprise diagnostics deals with the recognition and evaluation of all aspects of company processes and with the therapy devices (measures to improve the initial stage), facilities for a better recognition and effective regulation of the complicated processes of company management. It is considered to be a young science, therefore it draws from experiences of other sciences and continually improves the systematization of its method. The aim of the article is to show results of research (realization of stage analyses) in this topic area, our own deductions and to trigger a discussion which would raise enterprise diagnostics to a qualitatively higher level.